MULTI EVENT STUDY IN THE ERA OF PANDEMIC AND THE ERA OF BLACK ECONOMY IN INDONESIA - Kotambunan, Eunike R J; Gessal, Zevania E V (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
This study aims to look at financial market conditions whether there is a significant reaction from investors to the announcement of a lockdown or PSBB during the Covid-19 pandemic. In this study, an event study model will be used to see the impact caused by the COVID-19 pandemic on the stock market. The use of this method was chosen because this method can clearly detect any abnormal returns resulting from an event that has occurred. This research will look at the abnormal returns arising from the Covid-19 event. To calculate the abnormal return in this study using the market model. This study uses secondary data using stoock returns from 31 tourism companies listed on the IDX. The results show a comparioson of skewed returns before and after the Lockdown event, the outcome of the Covid-19 Pandemic leading to statistically significantt differences, as shows by the Wilcoxon Signed Ratings Test. This can happen if people in the market start selling their stock out of fear that the scenario cause by Covid-19 will spiral out of controlm not because they made a calculated decision to sell.